Optimalisasi Pengembangan Obyek Wisata Candi Untoroyono - Dewi Ayu Wisnu Wardani (Jayapangus Press, 2019)
The selection of this location with consideration of the development of the Untoroyono Temple into a tourist attraction supported by the potential to preserve Javanese culture by introducing the Javanese script, culture using the fingers, instilling the values ​​of Javanese character, and asor, tepo sliro, devoted to parents, inspiration to grow back the love of the country, so that the nation's children care more about Indonesia. Related to the attraction of managing the Temple as a tourist attraction, managing the Untoroyono Temple needs to be optimized with improvement, also providing facilities, creating comfort and increasing security so that income from management distribution will be higher and can be directly used for temple preservation. In this paper we will explore and review the formulation of the problem, namely: optimization of Untoroyono Temple tourism object development, (2) Factors that encourage optimization of Untoroyono Temple tourism object development, (3) the meaning of optimizing the development of Untoroyono Temple tourism objects. The results of the optimization of Untoroyono tourism object development Initially Optimized, creativity to beautify the temple, optimizing the year 2015 to the present, Steps in tourist visits at Untoroyono Temple, How to read the order of the Untoroyono Temple, Procedures for finding temples looking for tourists: Cleaning themselves, Filling the Guest Book, Filling the Box Charity, Wearing Jarik, Introduction to Batik Motifs and their meanings, Wearing hena using Javanese script, receiving explanations about Untoroyono Temple, conducting syailendra class / helping by Mr. Suhardi, Indonesian visitors on paper, Visitors are required to sing Indonesia Raya song, Gratitude to foster love soil, Aji Saka Commemoration, Untoroyono Temple's Jug Water Drinking, some people believe Untoroyono temple water can be used, making a more charismatic aura, Untoroyono Wedang Cantor's Distinctive Drink is made of Javanese acid and is useful for neutralizing poisons, improving blood circulation, protecting health and protecting fitness, braking right and get rid of pimples, lose weight, stay young and popular effective in warding off evil spirits, decorative variety for selfies, group photo session. An optimization of the development of the tourism objects at Untoroyono Temple is caused by factors that encourage both internal and external factors. Internal factors are factors supporting the mindset of the community, the creativity of the people of expression, and motivation to improve welfare. As external factors, namely the development of tourism, capitalism and the culture industry, the role of mass media and hegemony government. The Meaning of Optimization of Untoroyono Tourism Object Development: The Meaning of Religious, The Meaning of Cultural Preservation, The Meaning of Historical Identity, The Meaning of People's Welfare in the Village of Kalangan, The Meaning of Education.